PENERAPAN PEMBELAJARAN INKUIRI TERBIMBING TERHADAP PENINGKATAN KEMAMPUAN LITERASI SAINS PESERTA DIDIK - Hartono, Kristin Dwi Yulia; Sari, Dhita Ayu Permata (PENSA E-JURNAL: PENDIDIKAN SAINS, 2023)
The research aimed to describe the increase in scientific literacy skills on Vibration and Wave material for students of one of Public Junior High Schools in Sidoarjo after being taught the guided inquiry learning model. This research using pre-experimental design with the type of One Group Pretest-Posttest. The research subjects were 27 students in the class of VIII-D SMP. The instruments used were observation sheets of learning implementation, scientific literacy ability tests, and student response questionnaires. Implementation data analysis method by calculating the average score of each aspect based on implementation criteria. The data calculation method for increasing scientific literacy skills was using N-Gain. The method of analyzing student responses is by calculating the number of positive answers and their percentages. The results of the implementation of the guided inquiry learning model went very well with a mean score of 3.78. The Wilcoxon test gets an Asymp.Sig score of 0.000 (<0.05) so H1 is accepted so that there is a difference in the mean pretest and posttest, besides that positive rank shows an increase in value and indicates the effect of guided inquiry on increasing scientific literacy skills. The average N-gain score is 0.57 with moderate improvement criteria. Students gave a positive response to guided inquiry learning to increase scientific literacy skills with an average positive answer of 82.10% with very good criteria.